Membrane targeting of the yeast exocyst complex - Pleskot, Roman; Cwiklik, Lukasz; Jungwirth, Pavel; Žárský, Viktor; Potocký, Martin (Biochimica et biophysica acta, 2015)
The exocytosis is a process of fusion of secretory vesicles with plasma membrane, which plays a prominent role in many crucial cellular processes, e.g. secretion of neurotransmitters, cytokinesis or yeast budding. Prior to the SNARE-mediated fusion, the initial contact of secretory vesicle with the target membrane is mediated by an evolutionary conserved vesicle tethering protein complex, the exocyst. In all eukaryotic cells, the exocyst is composed of eight subunits - Sec5, Sec6, Sec8, Sec10, Sec15, Exo84 and two membrane-targeting landmark subunits Sec3 and Exo70, which have been described to directly interact with phosphatidylinositol (4,5)-bisphosphate (PIP2) of the plasma membrane. In this work, we utilized coarse-grained molecular dynamics simulations to elucidate structural details of the interaction of yeast Sec3p and Exo70p with lipid bilayers containing PIP2. We found that PIP2 is coordinated by the positively charged pocket of N-terminal part of Sec3p, which folds into unique Pleckstrin homology domain. Conversely, Exo70p interacts with the lipid bilayer by several binding sites distributed along the structure of this exocyst subunit. Moreover, we observed that the interaction of Exo70p with the membrane causes clustering of PIP2 in the adjacent leaflet. We further revealed that PIP2 is required for the correct positioning of small GTPase Rho1p, a direct Sec3p interactor, prior to the formation of the functional Rho1p-exocyst-membrane assembly. Our results show the critical importance of the plasma membrane pool of PIP2 for the exocyst function and suggest that specific interaction with acidic phospholipids represents an ancestral mechanism for the exocyst regulation.
Keywords: Cell Membrane; rho proteiny vázající GTP; vazba proteinů; podjednotky proteinů; Molecular Dynamics Simulation; Saccharomyces cerevisiae; vezikulární transportní proteiny; fosfatidylinositol-4,5-difosfát; exocytóza; Secretory Pathway; Exocytosis; mutace; rho GTP-Binding Proteins; Phosphatidylinositol 4,5-Diphosphate; Saccharomyces cerevisiae - proteiny; Protein Binding; simulace molekulární dynamiky; buněčná membrána; Vesicular Transport Proteins; sekreční dráha; Mutation; Kinetics; kinetika; Protein Subunits; Saccharomyces cerevisiae Proteins